Gobernando el pasado: el proceso de justicia transicional en México, 2001-2006. - Treviño Rangel, Javier (El Colegio de México A.C., 2014)
This paper explores the many factors that caused the process of transitional justice in Mexico to result in impunity. It examines the historical development of the process of transitional justice since the creation of the Special Prosecutor’s Office in 2001 until it was closed down in 2006. The guiding question in this paper is: what factors allowed this process of transitional justice to protect rather than punish perpetrators of past crimes in Mexico?